An excellent ozone-resistant polymethylvinylsiloxane coating on natural rubber by thiol-ene click chemistry - N. Y. Ning; Z. P. Zheng; L. Q. Zhang; M. Tian (eXPRESS Polymer Letters)
Natural rubber (NR) as renewable resource is a kind of cheap and versatile elastomer. A disadvantage of NR is that the ozone resistance is not good, which needs to be improved for its wider application. In this study, polymethylvinylsiloxane (PMVS) coating on natural rubber (NR) was realized for the first time by using thiol-ene click reaction under UV irradiation, simultaniously realizing the fast crosslinking of PMVS layer and the covalent crosslinking between PMVS layer and NR layer. As a result, a good interphase adhesion between PMVS coating and NR was obtained. The coating of the crosslinked PMVS layer on NR resulted in an obvious increase in the ozone resistance of NR. Our study provides a new and high efficient strategy to prepare elastomer materials with good ozone resistance.